Method development and validation for the quantification of dasatinib, erlotinib, gefitinib, imatinib, lapatinib, nilotinib, sorafenib and sunitinib in human plasma by liquid chromatography coupled with tandem mass spectrometry. (17th September 2012) - Lankheet, N. A. G.; Hillebrand, M. J. X.; Rosing, H.; Schellens, J. H. M.; Beijnen, J. H.; Huitema, A. D. R.
ABSTRACT To support pharmacokinetic‐guided dosing in individual patients, a fast and accurate method for simultaneous determination of anticancer tyrosine kinase inhibitors (TKIs) dasatinib, erlotinib, gefitinib, imatinib, lapatinib, nilotinib, sorafenib and sunitinib in human plasma was developed using high‐performance liquid chromatography and detection with tandem mass spectrometry (HPLC‐MS/MS). Stable isotopically labeled compounds of the eight different TKIs were used as internal standards. Plasma proteins were precipitated and an aliquot of supernatant was directly injected onto a reversed phase chromatography system consisting of a Gemini C18 column (50 × 2.0 mm i.d., 5.0 µm particle size) and then compounds were eluted with a gradient. The outlet of the column was connected to a triple quadrupole mass spectrometer with electrospray interface. Ions were detected in the positive multiple reaction monitoring mode. This method was validated over a linear range from 20.0 to 10, 000 ng/mL for erlotinib, gefitinib, imatinib, lapatinib, nilotinib and sorafenib, and from 5.00 to 2500 ng/mL for dasatinib and sunitinib. Results from the validation study demonstrated good intra‐ and inter‐assay accuracy (<13.1%) and precision (10.0%) for all analytes. This method was successfully applied for routine therapeutic drug monitoring purposes in patients treated with the investigated TKIs. Copyright © 2012 John Wiley & Sons, Ltd.